2008
DOI: 10.1103/physreva.78.042307
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of entangled states by quantum Markov processes

Abstract: We investigate the possibility of using a dissipative process to prepare a quantum system in a desired state. We derive for any multipartite pure state a dissipative process for which this state is the unique stationary state and solve the corresponding master equation analytically. For certain states, like the Cluster states, we use this process to show that the jump operators can be chosen quasi-locally, i.e. they act non-trivially only on a few, neighboring qubits. Furthermore, the relaxation time of this d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
818
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 699 publications
(828 citation statements)
references
References 34 publications
(55 reference statements)
7
818
1
2
Order By: Relevance
“…While the present work has focused on condensed matter aspects of realizing nonequlibirium (quasi-)condensates of interacting bosons and paired fermions in optical lattices, the present ideas are readily extended to spin systems, and promise a new avenue towards preparing interesting entangled states of qubits for quantum information [16]. On the atomic physics side, control via external fields offers interesting new possibilities of engineering a broad class of quantum jump operators (3), one example being phase imprinting a i → a i e iφi with a laser.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the present work has focused on condensed matter aspects of realizing nonequlibirium (quasi-)condensates of interacting bosons and paired fermions in optical lattices, the present ideas are readily extended to spin systems, and promise a new avenue towards preparing interesting entangled states of qubits for quantum information [16]. On the atomic physics side, control via external fields offers interesting new possibilities of engineering a broad class of quantum jump operators (3), one example being phase imprinting a i → a i e iφi with a laser.…”
Section: Discussionmentioning
confidence: 99%
“…the dark state is an eigenstate of the set of quantum jump operators with zero eigenvalue, which will be compatible with the dynamics induced by the Hamiltonian if (ii) H |D = E |D . Uniqueness of the dark state is guaranteed if there is no other subspace of the system Hilbert space which is invariant under the action of the operators c ℓ [15,16]. In fact, it can be shown that for any given pure state there will be a master equation so that this state becomes the unique steady state [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This formalism offers a natural setting for the simulation of open quantum systems and arXiv:1405.6049v3 [quant-ph] 28 May 2017 research in this direction has resulted in successful experimental demonstrations of the dissipative simulation of complex many-body spin models [27,28]. In addition, dissipative quantum computation has allowed for alternative approaches to state preparation [29]- [38] and universal quantum computation [39,40]. Importantly however, it has recently been shown that dissipative quantum computing is no more powerful than the traditional circuit model -the so called "Dissipative Church Turing Thesis" [41].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum fluctuations alone can give origin, at zero temperature, to quantum phase transitions [2] whose effects can experimentally be observed in a critical region at small but finite temperatures. Away from thermodynamic equilibrium engineered open quantum systems provide a more recent source of interest [3][4][5]. In these latter settings a controlled environment can be used to drive the system to a steady state whose properties depend on system and environment parameters.…”
Section: Introductionmentioning
confidence: 99%